2021
DOI: 10.1155/2021/6647959
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Bacteria on the Mobile Phones and Computer Keyboards of Healthcare University Students in Ghana

Abstract: Globally, mobile phones and computers (laptops and desktops) are indispensable part of human lives for communication, entertainment, and educational purposes. However, there are concerns about the increasing risk of bacterial contamination and antibiotic resistant trends from the surfaces of these devices. This study aims to assess bacterial contamination of mobile phones and computer keyboards and their resistant profile at the University of Ghana, Korle-Bu Campus, Accra. This was a cross-sectional study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…This outbreak could be due to the close contact of medical students with patients in educational hospitals and the possibility of bacterial transmission to computer keyboards. Bacterial contamination of the keyboards has posed a threat to public health so that according to researchers, the bacteria grown on keyboards of the computers are more dangerous for human health (2). In another survey from Sudan, coagulase-negative Staphylococci were isolated in 56% of cases, which was higher than our study (21).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This outbreak could be due to the close contact of medical students with patients in educational hospitals and the possibility of bacterial transmission to computer keyboards. Bacterial contamination of the keyboards has posed a threat to public health so that according to researchers, the bacteria grown on keyboards of the computers are more dangerous for human health (2). In another survey from Sudan, coagulase-negative Staphylococci were isolated in 56% of cases, which was higher than our study (21).…”
Section: Discussioncontrasting
confidence: 72%
“…Computers, smartphones, and laptops are electronic devices that receive information and provide results more quickly and accurately after analysis (1,2). The bacterial contamination of computer keyboards is high due to a large number of users and their hands-on connections with the keyboards.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prevalence is lower than the 40.2% reported in Tanzania [21]. Additionally, the prevalence is lower compared to 22.0% reported in eastern Uganda [22].…”
Section: Discussioncontrasting
confidence: 62%
“…and 6.7% E. coli . Overall, high rates of resistance to AMP (96.7%) and TET (75.8%) were observed, and E. coli showed AMR rates of 18.6% [ 29 ]. Acolatse et al also showed widespread contamination with ESBL- and carbapenemase- producing gram-negative bacteria in surface swabs from a tertiary Ghanaian hospital in 2022 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%